MESENCHYME AND MESOTHELIUM - Lewis, Warren H. (The Rockefeller University Press, 1923)
The migratory mesenchymal cells in cultures of the embryonic chick heart show all stages of transformation from the bipolar and multipolar reticular cells to the flat mesothelial forms. One can actually observe this change in form. Such mesothelial cells seem to differ from the mesenchymal cells only in form and not in structure, indicating that mesothelium is to be considered not as a tissue differentiated from the mesenchyme, but merely as a change or transformation in form. These observations, together with those of W. C. Clarke, indicate that, in the healing of wounds of the mesothelium lining the peritoneal, pleural, and serous cavities, new mesothelium may arise from the subjacent mesenchyme by the change in form of its cells, and that the repair after abrasions of the mesothelium is not necessarily brought about by a spreading of the adjacent mesothelium over the wound, such as occurs in repair of skin wounds.